Emergency Medicine Cases in Underwater and Hyperbaric Environments: The Use of in situ Simulation as a Learning Technique - Paganini, Matteo; Mormando, Giulia; Savino, Sandro; Garetto, Giacomo; Tiozzo, Giulia; Camporesi, Enrico M.; Fabris, Fabrizio; Bosco, Gerardo (Frontiers in Physiology, 2021)
Introduction: Hyperbaric chambers and underwater environments are challenging and at risk of serious accidents. Personnel aiming to assist patients and subjects should be appropriately trained, and several courses have been established all over the world. In healthcare, simulation is an effective learning technique. However, there have been few peer-reviewed articles published in the medical literature describing its use in diving and hyperbaric medicine. Methods: We implemented the curriculum of the Master's degree in hyperbaric and diving medicine held at the University of Padova with emergency medicine seminars created by the faculty and validated by external experts. These seminars integrated traditional lectures and eight in-situ simulation scenarios. Results: For the hyperbaric medicine seminar, simulations were carried out inside a real hyperbaric chamber at the ATIP Hyperbaric Treatment Centre, only using air and reproducing compression noise without pressurization to avoid damages to the manikins. The four scenarios consisted of hyperoxic seizures, pneumothorax, hypoglycemia, and sudden cardiac arrest. Furthermore, we added a hands-on session to instruct participants to prepare an intubated patient undergoing hyperbaric oxygen treatment with a checklist, and simulating the patient transfer inside and outside the hyperbaric chamber. The diving medicine seminar was held at the Y-40 The Deep Joy pool in Montegrotto Terme (Italy), also involving SCUBA/ breath-hold diving (BHD) instructors to rescue subjects from the water. These diving medicine scenarios consisted of: neurologic syndrome (“taravana/samba”) in BHD; drowning of a breath-hold diver; pulmonary barotrauma in BHD; decompression illness in a SCUBA diver. Conclusion: With this experience, we report the integration of simulation in the curriculum of a teaching course in diving and hyperbaric medicine. Future studies should be performed to investigate learning advantages, concepts’ retention, and satisfaction of participants.